Pemberdayaan Ibu Hamil Trimester III melalui Konseling Persiapan Persalinan Berbasis Respectful Maternity Care (RMC) - Susianti Susianti; Arifa Usman; Ayu Irawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Empowering pregnant women in their third trimester through Respectful Maternity Care-based childbirth preparation counseling is a relevant promotive and preventive strategy for improving maternal health. This counseling not only provides knowledge about the signs of labor, stages of labor, pain management options, and birth planning, but also equips mothers with an understanding of their rights in midwifery care. Childbirth preparation education often focuses solely on clinical aspects and fails to fully address the psychosocial aspects and the rights of mothers as service recipients. This has the potential to lead to an unpleasant childbirth experience and even contribute to disrespect and abuse during labor. This counseling can equip mothers with an understanding of their rights in midwifery care. With an empathetic, participatory, and woman-centered approach, pregnant women are expected to be able to recognize their needs, convey their preferences, and communicate effectively with health workers. The purpose of this counseling is to improve pregnant women's knowledge before and after being empowered in their third trimester through Respectful Maternity Care-based childbirth preparation counseling.